2010
DOI: 10.1007/s11244-010-9495-7
|View full text |Cite
|
Sign up to set email alerts
|

TPR and EXAFS Studies on Na-Promoted Co/ZnO Catalysts for Ethanol Steam Reforming

Abstract: Na-promoted Co/ZnO catalysts were prepared and applied to ethanol steam reforming. TPR and EXAFS analysis demonstrated that Na promoter effectively enhanced the reducibility of Co phase on ZnO with better catalytic activity and selectivity towards H 2 than unpromoted Co/ZnO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…As a result, the authors suggested that Co 2+ should be minimized. This is supported by investigations of Kim et al, in which metallic Co was responsible for ESR reaction, and Na was used to enhance the reducibility of cobalt and improve catalyst performance. , Ticianelli and co-workers used noble metal promoters to facilitate Co reduction via H 2 spillover. Moreover, Zn promoter was added; nevertheless, it showed an opposite effect on different supports: Zn addition on ZrO 2 inhibited the oxidation of Co 0 by steam, thus maintaining a high Co 0 /Co 2+ ratio to suppress CH 4 , whereas Zn addition on CeO 2 facilitated the oxidation of Co 0 as well as CH x and CO via the enhanced support oxygen mobility, leading to higher CO 2 selectivity despite weakened C–C bond cleavage activity. , To date, results have indicated the involvement of the oxidation state of cobalt in determining the activity, selectivity, and stability of Co-based catalysts in the ESR reaction. Nevertheless, regarding the different support materials and their interactions with cobalt in these studies, no conclusion could be made by far, which calls for more investigations upon the intrinsic active sites in working cobalt catalysts under ESR conditions.…”
Section: Ethanol Reformingmentioning
confidence: 79%
See 1 more Smart Citation
“…As a result, the authors suggested that Co 2+ should be minimized. This is supported by investigations of Kim et al, in which metallic Co was responsible for ESR reaction, and Na was used to enhance the reducibility of cobalt and improve catalyst performance. , Ticianelli and co-workers used noble metal promoters to facilitate Co reduction via H 2 spillover. Moreover, Zn promoter was added; nevertheless, it showed an opposite effect on different supports: Zn addition on ZrO 2 inhibited the oxidation of Co 0 by steam, thus maintaining a high Co 0 /Co 2+ ratio to suppress CH 4 , whereas Zn addition on CeO 2 facilitated the oxidation of Co 0 as well as CH x and CO via the enhanced support oxygen mobility, leading to higher CO 2 selectivity despite weakened C–C bond cleavage activity. , To date, results have indicated the involvement of the oxidation state of cobalt in determining the activity, selectivity, and stability of Co-based catalysts in the ESR reaction. Nevertheless, regarding the different support materials and their interactions with cobalt in these studies, no conclusion could be made by far, which calls for more investigations upon the intrinsic active sites in working cobalt catalysts under ESR conditions.…”
Section: Ethanol Reformingmentioning
confidence: 79%
“…This is supported by investigations of Kim et al, in which metallic Co was responsible for ESR reaction, and Na was used to enhance the reducibility of cobalt and improve catalyst performance. 631,632 Ticianelli and co-workers used noble metal promoters to facilitate Co reduction via H 2 spillover. 633−635 Moreover, Zn promoter was added; nevertheless, it showed an opposite effect on different supports: Zn addition on ZrO 2 inhibited the oxidation of Co 0 by steam, thus maintaining a high Co 0 /Co 2+ ratio to suppress CH 4 , whereas Zn addition on CeO 2 facilitated the oxidation of Co 0 as well as CH x and CO via the enhanced support oxygen mobility, leading to higher CO 2 selectivity despite weakened C−C bond cleavage activity.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…The nature of the catalyst support also influences the selectivity of the APR process by catalyzing parallel dehydration pathways and formation of alkanes, as was described above. It was observed that a more acidic catalyst, such as SiO 2 –Al 2 O 3 , leads to high selectivity of alkane formation, whereas the more basic/neutral support (e.g., Al 2 O 3 ) favors hydrogen production. ,, Furthermore, catalytic activity decreases with reaction duration by carbon deposition on the catalyst surface so the addition of alkali metals (1 wt % of Na) exhibited both catalyst activity toward hydrogen formation and stability . Along with the acidic/basic nature of the catalyst/support, also the pH in the reaction solution, originating from compound formation during the reaction, affects the selectivity of APR.…”
Section: Hydrothermal Reactions Of Agricultural and Food Processing W...mentioning
confidence: 99%
“…The reaction network associated to the ESR is complex, both from the mechanistic and the thermodynamic points of view 7 for the practical application of this process, which can be partly solved by the addition of alkaline promoters [8][9][10] . All these factors explain the need for extensive research of appropriate catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…They show different dependence relationships on reaction conditions, and their promotion depends on different functionalities of the catalyst. In addition, formation of coke precursors from several of the compounds involved makes deactivation an important issue for the practical application of this process, which can be partially solved by the addition of alkaline promoters. All of these factors explain the need for extensive research of appropriate catalysts. Many studies have been focused on the ESR using supported nickel, cobalt, and noble-metal catalysts. An efficient catalyst for hydrogen production from ethanol has to dissociate the C–C bond at reasonably low temperatures, and it has to maintain a low CO concentration and be stable under catalytic operation.…”
Section: Introductionmentioning
confidence: 99%